Synthesis of Faujasite from Fly Ash and its Applications for Hydrocracking of Petroleum Distillates - Sutarno Sutarno; Yateman Arryanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2007)
The synthesis of faujasite from fly ash and its application for hydrocracking catalyst of heavy petroleum distillates have been performed. Faujasite was synthesized from fly ash by hydrothermal reaction in alkaline solution via combination of reflux pretreatment of fly ash with HCl and fusion with NaOH. The preparation of nickel containing catalysts by ion exchange method under similar initial concentration of nickel resulted higher amount of nickel loaded on faujasite than those on zeolite Y, however, the structural damage of faujasite was higher than those of zeolite Y. In the hydrocracking of heavy petroleum distillates over Ni-faujasite and Ni-zeolite Y catalysts, the conversion of heavy gas oil fraction was the most pronounced. The selectivity toward hydrocarbons in the range of gasoline and kerosene obtained over Ni-faujasite catalyst was lower compared to those of Ni-zeolite Y reference catalyst. © 2007 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)